Reconstruction Methods and Complications of Esophagogastrostomy and Jejunal Interposition in Proximal Gastrectomy for Gastric Cancer: A Meta-Analysis. (16th January 2020) - Du, Nan; Wu, Pei; Wang, Pengliang; Du, Yuwei; Li, Kai; Wang, Zhenning; Xu, Huimian; Zhu, Zhi
Abstract : Background . Proximal gastrectomy is used for the treatment of primary gastric cancer by open or laparoscopic surgery in the upper third of the stomach. Esophagogastrostomy (EG) or jejunal interposition (JI) is widely used in various reconstruction methods after proximal gastrectomy. We conducted a meta-analysis of EG and JI for treatment of gastric cancer. Materials and Methods . A search of PubMed, Embase, MEDLINE, J-STAGE, and Cochrane Library identified retrospective series on EG and JI. Weight mean differences (WMDs), odds ratios (ORs), and 95% confidence intervals (CIs) were used to analyze the operation-related data and postoperative complications. Heterogeneity was evaluated by the I 2 test, and potential publication bias was assessed with Egger regression tests and sensitivity analysis. Results . Eight studies were selected, and 496 patients were included. EG group benefits were 44.81 min shorter operating time (P < 0.001 ), 56.58 mL less blood loss (P = 0.03 ), and 7.4 days shorter hospital stay time (P < 0.001 ) than the JI group. Between the two groups, there was no significant difference in anastomotic leakage; otherwise, the EG group had a lower risk of anastomotic stenosis (OR = 0.44, 95 % CI = 0.20 to 0.97, P = 0.04 ), lower risk of intestinal obstruction (OR = 0.07, 95 % CI = 0.01 to 0.43, P = 0.004 ), and higher risk of reflux esophagitis (OR = 2.47, 95 % CI = 1.07 to 5.72, P = 0.03 ). Conclusion . The results of our study indicated that EG has significant advantages during the perioperative period and in short-term outcomes compared to JI.